Gambling in Spain: the need for a geographical perspective - Arsenio Villar Lama (Asociación Española de Geografía, 2021)
The social practice of games of chance and gambling can be read in an interesting variety of ways in the area of the Social Sciences. One is the geographical perspective, which highlights the spatial repercussions of this form of recreation. However, in Spain, very little scientific literature exists on the topic, which justifies the appropriateness of this contribution with the purpose of establishing an initiatory conceptual and methodological framework. A variety of statistical and legal sources are treated to establish three levels of analysis: first, the position of games of chance and gambling in Spain in the international context; second, location patterns in Spain at the regional level, and third, the spatial aspects of the different legal norms at the autonomous community level. To conclude, games of chance and gambling are a deep-rooted form of recreation in Spain and offer interesting lines of geographical research, although it would be desirable for the quality, variety, and accessibility of data to be improved.